Shooting at a moving target: phase equilibria modelling of high‐temperature metamorphism. (10th February 2016) - Guevara, V. E.; Caddick, M. J.
Abstract: Thermodynamic modelling and calculation of P–T pseudosections are commonly employed for quantifying the P–T evolution of metamorphic rocks. A key assumption involved in interpreting a P–T pseudosection is that the bulk‐rock composition used is representative of the effective bulk composition (EBC) from which apparently equilibrated mineral assemblages grew. Choosing an EBC can be difficult in cases where the rock has evolved significantly throughout the P–T history and has become domainal for whatever reason (e.g. loss of fluid and/or melt), particularly at suprasolidus conditions. During partial melting, melt migration may not only change the bulk composition by melt loss but also may generate local variations due to the variable consumption/loss of melt from domain to domain to create volumes of rock that were once internally equilibrated in the presence of a grain boundary melt, but which departed from equilibrium as inter‐granular mobility was slowed by local reductions in melt volume. As well as careful consideration of an EBC, the results of thermodynamic modelling are highly dependent on the specific thermodynamic data set and solution models used, as updates to these data sets may lead to substantially different calculated phase equilibria. This contribution addresses: (1) how consideration of evolving EBCs at multiple scales of observation can be used to resolve the history of complex high‐grade rocks, and (2) how use of different thermodynamic data sets and a–x models (i.e.thermocalc ds5.5 v . ds6) can result in different interpretations of metamorphic evolution. This study investigates the evolution of a mineralogically heterogeneous and texturally complex hand sample of granulite from the Gruf Complex (Central Alps). At the hand‐specimen scale, an EBC can be identified and used to constrain the P–T conditions at which the 'whole rock' was last in mutual equilibrium, in the presence of intergranular melt that has subsequently been lost or consumed. Smaller macrodomains ( cm scale) and microdomains ( mm scale) can be identified that represent subsequent evolution during and after melt channelization and loss, and P–T pseudosections can be calculated for the compositions of these domains. Using this approach reveals that the sample experienced a clockwise P–T path marked by near‐isothermal decompression following attainment of peak UHT conditions ( 960 °C, 8.5 kbar). The approach enables construction of a P–T history of a rock for which P–T pseudosections are otherwise difficult to interpret. Thermodynamic modelling using ds6 yields similar results to those stated above, but suggests: (1) near‐isothermal decompression occurred over a wider pressure range ( 0.5 kbar v . 1.5 kbar), and (2) that not all microdomains record this part of the P–T evolution.